Learning gain in higher education (International perspectives on higher education research, 2021)
As students are bearing an increasing proportion of the costs of their participation in higher education, increasing attention has been paid nationally and internationally to the issue of what higher education does for its students. What do students gain from engaging in higher education, and how might this be accurately measured? This volume explores the latest thinking, research and practice on this topic from across the globe. Acknowledging that institutions of higher education, along with national governments and international organizations, are closely concerned with the answers to these questions, the authors demonstrate how it is critically important to be able to demonstrate convincingly and transparently how students have progressed, and what measurable skills and knowledge they have acquired.